Minutes of the 3rd Meeting of BRAC University Board of Trustees (BoT) - Board of Trustees (BoT), BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of the Minutes of 2nd Meeting of Board of Trustees. 2. Review of the progress of decisions of the 2nd Meeting of Board of Trustees. 3. Approval of the Minutes of 3rd and 4th Meeting of BRACU Syndicate. 4. Approval of the Minutes of 43rd Meetings of Academic Council (AC). 5. Approval of the Revised Syllabus of Post-Graduate Program on Disaster Management (PPDM). 6. Approval of the Minutes of the 27th Meeting of Finance Committee. 7. Approval of the Draft Annual Financial Statements. 8. Approval of the Minutes of the 2nd and 3rd Meeting of Disciplinary Committee. 9. Approval of the Minutes of the Faculty Appointment Committee Meeting. 10. Approval of the Minutes of the Staff Appointment Committee Meeting. 11. Preparation for the 7th Convocation. 12. Appointment of the Treasurer, BRACU. 13. Review of the Maternity Leave Policy. 14. Progress on Permanent campus. 15. Miscellaneous: 15.1 Increasing Hostel Accommodation for Students. 15.2 Review of Statute, Organogram and Terms of Conditions of Service of BRACU. 15.3 Reorganization of Institutes and Schools. 15.4 Space Problem of BRACU. 15.5 Discussion on Gender Studies.